COLLABORATIVE GOVERNANCE DALAM PENGAKUAN DAN PERLINDUNGAN MASYARAKAT HUKUM ADAT DI DESA KOTO SENTAJO KECAMATAN SENTAJO RAYA KABUPATEN KUANTAN SINGINGI TAHUN 2021-2022 - Gustrianti, Helsi; Asrida, Wan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Kuantan Singingi regency is one of the region that has the outhority to implement Minister of Home Regulation Number 52 0f 2014 concerning Guidelines for Recognition and Protection of Customary Law Community because community of Kuantan Singingi Regency are stil very strong in their customs and uphold traditional values. Such as the role of traditional stakeholders which is very important not only for their children and nephew but also plays a role in the assembely or institution collect “ tigo tungku sejorangan or tali bapilin tigo” which isa philosophy in development involving the government, cleric and traditional figure, This research aims to deternine the process of collaborative governance in the recognition and protection of customary law community in Koto Sentajo Village, Sentajo Raya District, Kuantan Singingi Regency. The thory used is a collaboration of Ansel and Gash. The research method used is qualitative by explaning descriptive. The location of the research is in Koto Sentajo Village, Sentajo Raya Dstrict, Kuantan Singingi Regency. The type of research data used is primary data obtained from research informants and secondary data obtaired from related documents that support the research process. The result of this research is a collaborative governane process in the recognition and protection of customary law community in Koto Sentajo Village Sentajo Raya District Kuantan Singingi Regency in 2021-2022 that face to face dialoque and building trust has been carried out. However, the collaborative governance process has not been effective because several indicators are not yet optimal in the commitment indicators to process, share understanding and intermediate outcome in the recognition and protection of customary law community. Keywords : Collaborative Governance,Customary Law Community, Regional Government